Losing a child to adolescent cancer: A register‐based cohort study of psychotropic medication use in bereaved parents. (11th October 2022) - Hovén, Emma; Ljungman, Lisa; Sveen, Josefin; Skoglund, Charlotte; Ljungman, Gustaf; Ljung, Rickard; Wikman, Anna
Abstract: Purpose: To investigate the short‐ and long‐term risk of psychotropic medication use in parents who lose a child to cancer diagnosed in adolescence. Methods: This is a Swedish nationwide register‐based study including 184 bereaved mothers and 184 bereaved fathers of 184 children diagnosed with cancer in adolescence. Logistic regression analyses, adjusted for sociodemographic characteristics and history of mental health problems, were performed to estimate risk of a prescription of psychotropic medication (anxiolytics, hypnotics/sedatives, antidepressants) in cancer‐bereaved parents from 1 year before to 5 years after the child's death, with a general population sample of non‐bereaved parents ( n  = 3291) as referents. Results: At the year of the child's death, 28%–36% of mothers and 11%–20% of fathers had a prescription of anxiolytics, hypnotics/sedatives or antidepressants. The corresponding percentages for non‐bereaved mothers and fathers were 7%–12% and 4%–7%, respectively. Compared to non‐bereaved mothers, bereaved mothers showed higher odds of prescriptions from 1 year before up to four (anxiolytics) and 5 years (hypnotics/sedatives and antidepressants) after the child's death. Bereaved fathers showed higher odds than non‐bereaved fathers of prescriptions from 1 year before up to the year of (anxiolytics and hypnotics/sedatives) and 1 year after (antidepressants) the child's death. No differences in odds between bereaved and non‐bereaved fathers were found at 2 years after the child's death. Being unmarried, born outside Sweden, and having a history of mental health problems were associated with higher odds of prescribed medications. Conclusions: Indicative of mental health problems of clinical importance, cancer‐bereaved parents had a higher prevalence of use of psychotropic medication. A decrease in medication use was evident with time, but still at 5 years after the child's death mothers displayed a higher use while fathers showed no difference to non‐bereaved fathers after 2 years.